Perception of Beauty - Peaslee Levine, Martha (IntechOpen, 2017)
The authors in this book ask us to consider whether the perception of beauty has been defined by our genetics and culture over the years - has it grown and changed? Do certain neural connections define our emotional reactions to beauty? Does beauty follow any rules or laws? Can the aspiration toward beauty be detrimental? Can we divorce ourselves from dictates and sink into a mindful connection with our internal beauty? Can we move from the superficial where "beauty is only skin deep" to an intense appreciation of beauty in all of its variations. The Perception of Beauty will lead to a deeper understanding and contemplation of nature, art, and the world around us.